2010
DOI: 10.1007/s10552-010-9679-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in arsenic intake from water has different impacts on lung cancer and bladder cancer in an arseniasis endemic area in Taiwan

Abstract: Reduction in arsenic intake from water has a positive impact on the incidence of both lung and bladder cancer; however, while RR for lung cancer has dropped to below 2, RR for bladder cancer remained at around 5. The difference may be because (1) there are other risk factors beside the well-water intake or (2) bladder cancer may have longer latency period for excessive arsenic exposure than lung cancer. More studies are required to understand the causes behind the difference in RR for these two types of cancer. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…In northern Chile, lung cancer rate ratios did not peak until at least 30 years after high exposures began [27] and remain very high (OR = 4.4, 95% CI = 2.6–7.4) nearly 40 years after high exposures ended [28]. Other studies have also found latency periods of 20 years or more [12,16,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…In northern Chile, lung cancer rate ratios did not peak until at least 30 years after high exposures began [27] and remain very high (OR = 4.4, 95% CI = 2.6–7.4) nearly 40 years after high exposures ended [28]. Other studies have also found latency periods of 20 years or more [12,16,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, new studies have shown a decreased risk of bladder cancer after a reduction of arsenic intake from drinking water in Taiwan and Argentina (Su et al, 2011; Pou et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Childhood liver cancer MRRs were 9–14 times higher for those exposed as young children as compared with controls (Liaw et al 2008). Other reports of latency periods extending over 50 years include skin cancer (Haque et al 2003), urinary cancers (Bates et al 2004; Chen CL et al 2010b; Marshall et al 2007; Su et al 2011), and lung cancer (Marshall et al 2007; Su et al 2011). For example, peak SMRs for childhood liver cancer and bronchiectasis were 14.1 and 50.1 times higher, respectively, for individuals exposed to arsenic in utero and during childhood as compared with individuals exposed during other periods of their lives (Table 4) (Smith et al 2006).…”
Section: Varied Susceptibilitiesmentioning
confidence: 99%